1996
DOI: 10.2323/jgam.42.17
|View full text |Cite
|
Sign up to set email alerts
|

A consideration about the origin of aphid intracellular symbiont in connection with gut bacterial flora.

Abstract: In an attempt to investigate the origin of the intracellular symbiont of the aphid (Buchnera), aphid gut aerobic bacteria were isolated, and their phylogenetic relations to other prokaryotes were examined based on nucleotide sequences of 16S rDNA. It turned out that there are seven aerobic bacterial groups which constitute major flora of the aphid's gut. As three of the isolated bacteria were identified as members of the family Enterobacteriaceae, and share the common ancestor with the intracellular symbiont, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 19 publications
3
55
0
Order By: Relevance
“…Strains X 001, X 081, X 151, X 171 and X 181 were isolated from the guts of healthy apterous aphids as previously described (Harada et al, 1996). Whole bodies of the insect, which were surface-sterilized by dipping into 70% ethanol for 5 min, were washed in sterilized Carlson's solution (0.7% NaCI (w/v), 0.02% KCI (w/v), 0.02% CaCl2.2H2O (wlv), 0.01% MgCl2 • 6H2O (w/v), 0.02% NaH2PO4 (w/v), 0.012% NaHCO3 (w/v) and 0.8% glucose (w/v)), and lightly homogenized in the same solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strains X 001, X 081, X 151, X 171 and X 181 were isolated from the guts of healthy apterous aphids as previously described (Harada et al, 1996). Whole bodies of the insect, which were surface-sterilized by dipping into 70% ethanol for 5 min, were washed in sterilized Carlson's solution (0.7% NaCI (w/v), 0.02% KCI (w/v), 0.02% CaCl2.2H2O (wlv), 0.01% MgCl2 • 6H2O (w/v), 0.02% NaH2PO4 (w/v), 0.012% NaHCO3 (w/v) and 0.8% glucose (w/v)), and lightly homogenized in the same solution.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, aerobic bacteria were isolated from aphid gut in order to investigate insect-bacteria interaction, and seven groups were identified as major constituents of the gut flora of the pea aphid, Acyrthosiphon pisum (Harada et al, 1996). Based on the molecular phylogenetic analyses of 16S rDNA, three of the seven bacterial groups were identified as members of the family Enterobacteriaceae, and tentatively named bacterium T, W and X. DNA-DNA hybridization testing and a phylogenetic tree of 16S rDNA indicated that bacterium T was identical to Erwinia herb/cola (Harada et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some genera have been investigated in detail, e.g. Yersinia (Ibrahim et al, 1994), Salmonella (Chang et al, 1997 ;Christensen et al, 1998), Serratia (Dauga et al, 1990 ;Harada et al, 1996) and Erwinia (Kwon et al, 1997 ;Hauben et al, 1998), the genus Klebsiella has not been analysed extensively (Carter et al, 1999). The taxonomy of the genus Klebsiella was characterized by a nomenclature reflecting its colourful history.…”
Section: Introductionmentioning
confidence: 99%
“…Besides Buchnera, aphids often harbor additional bacteria that are commonly referred as secondary (S) endosymbionts. These bacteria can be found in the aphid guts, in tissues surrounding the P bacteriocytes (or even invading the P bacteriocytes themselves), and in specialized S bacteriocytes (10)(11)(12). These endosymbionts are also subject to vertical transmission (13), but their patchy distribution among aphid populations implies that they, unlike Buchnera, also undergo horizontal transmission (10).…”
mentioning
confidence: 99%